Int cos(sqrx) dx
First we
will assume that:
t = sqrt x ==> dt =
-1/2sqrx
=
-1/2tdx
==> dx =
-2tdt
==> Int cos(sqrtx) dx = Int cos(t) *-2tdt = -2
Int t*cos(t) dt...(1)
Now we will integrate t*cos(t)
t
Let u = t ==> du =
dt
Let dv = cost dt ==> v =
sint
==> Int u dv = u*v - Int v
du
==> Int t*cost dt = t*sint - Int sint
dt
==> Int tcost dt = t*sint + cost
.........(2)
Now we will substitute (2) into
(1).
==> Int cos(sqrtx) dx = Int cos(t) *-2t dt = -2
Int t*cos(t) dt
==> Int cos(sqrtx)dx = -2[ t*sin(t)
+ cos(t)] + C
==> INt cos(sqrx) dx = -2t*sin(t)
-2cos(t) + c
Now we will substitute with t=
sqrtx
==> Int cos(sqrtx) dx =
-2sqrt(x)*sin(sqrtx) - 2cos(sqrtx) + C
No comments:
Post a Comment